Sizing and identification of nanoparticles by a tapered fiber. Issue 57 (24th September 2018) - Pan, Huiling; Zhang, Weina; Lei, Hongxiang
Abstract : Nanoparticles with different sizes or with different refractive index can be distinguished using an optical tapered fiber. Abstract : There is a strong desire for sizing and identification of nanoparticles in fields of advanced nanotechnology and environmental protection. Although existing approaches can size the nanoparticles, or identify nanoparticles with different refractive indexes, a fast and simple method that combines the two functions still remains challenges. Here, we propose a versatile optical method to size and identify nanoparticles using an optical tapered fiber. By detecting reflection signals in real time, 400–600 nm SiO2 nanoparticles can be sized and 500 nm SiO2, PMMA, PS nanoparticles can be identified. This method requires only an optical tapered fiber, avoiding the use of elaborate nanostructures and making the device highly autonomous, flexible and compact. The demonstrated method provides a potentially powerful tool for biosensing, such as identification of nano-contaminant particles and biological pathogens.